The Student’s Barriers in Speaking English at STIKes Darmais Padangsidimpuan - Bincar Nasution; Ahmad Laut Hasibuan; Azhary Tambusai (PT Inovasi Pratama Internasional, 2022)
Based on the concept presented in the introduction, it can be concluded that there are many difficulties students encounter when learning the English language, especially as a foreign language because the language is used in any condition and certain people which is not in daily activities. Therefore, I interest to dig deeper into that obstacle experienced by students on language skills, especially on speaking skill, which is about the student‟s barriers in speaking English. This research, an exploratory sequential mixed method research (MMR) design was selected in order to broadly explore students' barriers in speaking English. The observations showed that students‟ main barrier was individual barriers; nervous, lack of vocabulary, feel unable to speak precisely, grammar error, underestimated in presenting information in order, lack of confidence. The students confirmed that individual barrier was the main barriers they face, and then language barrier, environment also interpersonal barriers followed. Since they did not feel able to speak English in a natural way, and thinking about how to pronounce correctly a word or how to use the correct grammar structures, they said that it was difficult to grow the confident.